Cost‐effectiveness analysis of papillary thyroid cancer surveillance. Issue 23 (17th August 2015) - Wang, Laura Y.; Roman, Benjamin R.; Migliacci, Jocelyn C.; Palmer, Frank L.; Tuttle, R. Michael; Shaha, Ashok R.; Shah, Jatin P.; Patel, Snehal G.; Ganly, Ian
Abstract : BACKGROUND: The recent overdiagnosis of subclinical, low‐risk papillary thyroid cancer (PTC) coincides with a growing national interest in cost‐effective health care practices. The aim of this study was to measure the relative cost‐effectiveness of disease surveillance of low‐risk PTC patients versus intermediate‐ and high‐risk patients in accordance with American Thyroid Association risk categories. METHODS: Two thousand nine hundred thirty‐two patients who underwent thyroidectomy for differentiated thyroid cancer between 2000 and 2010 were identified from the institutional database; 1845 patients were excluded because they had non‐PTC cancer, underwent less than total thyroidectomy, had a secondary cancer, or had <36 months of follow‐up. In total, 1087 were included for analysis. The numbers of postoperative blood tests, imaging scans and biopsies, clinician office visits, and recurrence events were recorded for the first 36 months of follow‐up. Costs of surveillance were determined with the Physician Fee Schedule and Clinical Lab Fee Schedule of the Centers for Medicare and Medicaid Services. RESULTS: The median age was 44 years (range, 7‐83 years). In the first 36 months after thyroidectomy, there were 3, 44, and 22 recurrences (0.8%, 7.8%, and 13.4%) in the low‐, intermediate‐, and high‐risk categories, respectively. The cost of surveillance for each recurrence detected was US 147, 819, US 22, 434, and US 20, 680, respectively. CONCLUSIONS: The cost to detect a recurrence in a low‐risk patient is more than 6 and 7 times greater than the cost for intermediate‐ and high‐risk PTC patients. It is difficult to justify this allocation of resources to the surveillance of low‐risk patients. Surveillance strategies for the low‐risk group should, therefore, be restructured. Cancer 2015;121:4132–4140. © 2015 American Cancer Society . Abstract : The cost to detect a recurrence in a low‐risk patient is more than 7 times greater than the cost for a high‐risk papillary thyroid cancer patient. It is difficult to justify this allocation of resources, and surveillance strategies for the low‐risk group should be reviewed.